Changes in Status and Performance Over Time for Students With Specific Learning Disabilities. (February 2019) - Tindal, Gerald; Anderson, Daniel
With the shift from No Child Left Behind (NCLB) to Every Student Succeeds Act (ESSA), accountability models are being changed. Given the past 15 years of reporting on student subgroups and 10 years using various growth models, accountability systems can now be better informed. In this study, we analyze identification and services of students with specific learning disabilities (SLDs). First, we document the degree to which they are identified and receive special services for three cohorts and then document changes in proficiency and growth on a state test. Next, we use two measures of growth to document progress: a transition matrix and a multilevel model. We found that some students change in their identification as SLDs over three grades with resulting differences in special education supports, but the effect is negligible on growth. Accountability systems, therefore, may not need to be based on complex models using time-varying student characteristics.